Perancangan Informasi Akuntansi Pinjaman Secara Kredit Pada Koperasi Simpan Pinjam Bina Mitra - Wawan Haryanto; Rini Fitria; Siswidiyanto Siswidiyanto (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2020)
Information systems have a positive impact on the advancement of life in the technology industry, making it easier for corporate human resources to be fast and precise. For example, companies that currently use applications in their electronic devices or software and drivers to streamline their products and products. All of that is done in order to achieve a goal that is to facilitate the performance of humans, organizations or companies in exchanging data and information and its distribution. Koperasi Bina Mitra Usaha Jatisari is in need of an accounting information system that supports and provides satisfactory services for its members. Koperasi Bina Mitra Usaha Jatisari is a cooperative engaged in several fields, one of which is a loan unit on credit. For this reason, researchers designed the Loan Accounting Information System. Koperasi Bina Mitra Usaha Jatisari method used by the buyer is swot analysis for the design method using unified Modeling language (UML) and blackbox testing system testing methods. This study makes it easy to record loan applications, member loan data, payments, data input, calculations and report generation.